PENGENALAN BAHASA INGGRIS MELALUI LAGU DI TPQ AL KAUTSAR 1 - Arini Hidayah; Budi Purnomo; Yunita Widiyantari; Eka Susylowati (LPPM Universitas Bina Bangsa, 2021)
The goal of the community service entitled Introduction to English through songs at TPQ Al Kautsar 1 is to introduce English vocabulary through songs to improve students' comprehension of English. English song content taught at TPQ Al Kautsar 1 has never been obtained. The first stage was to conduct a series of English language introduction activities for pupils using songs to train pupils at TPQ Al Kautsar. Community service increased pupils' English comprehension. TPQ Al Kautsar pupils, based on observations made by the community service team, there are indications of increased English comprehension among pupils at TPQ Al Kautsar 1.